Studies of Platelet Aggregation, Plasma Adenosine Diphosphate Breakdown and Blood Coagulation in Magnesium Deficient Calves and Rats - Stevenson, M. M; Yoder, I. I (Thrombosis and Haemostasis, 1970)
ADP-induced platelet aggregation and the breakdown of ADP in platelet-poor plasma of normal and magnesium deficient calves and rats have been studied. There was no statistically significant difference in ADP-induced platelet aggregation between the treated and untreated groups of animals. There was a significant difference in the ADP breakdown in platelet poor plasma of magnesium deficient rats as compared to the untreated animals. The platelet count of the magnesium deficient calves and in the citrated platelet-rich plasma of the magnesium deficient rats was not different from the normal. The thrombin clotting and partial thromboplastin times were significantly shortened in the magnesium deficient calves, but the prothrombin time was not affected. These findings suggest that pathological alterations in the serum magnesium levels that are still compatible with life do not influence adenosine diphosphate-induced platelet aggregation but do affect the breakdown of adenosine diphosphate in the plasma of rats. Just as magnesium administration may produce an anticoagulant effect, so may magnesium depletion produce a procoagulant effect in the blood of animals rendered magnesium deficient by diet. The clinical implications of this are discussed.